Administration of Leptin Increases the Level of Follicle Stimulating Hormone (FSH) and Development of Ovarian Follicles in Postpartum Anestrus of Bali Cattle - Pradnyana, Dewi Indira Laksmi; Pemayun, Tjok G. O.; Damriyasa, I Made; Dharmawan, N. S. (BALI MEDICAL JOURNAL, 2016)
Background: Leptin is a metabolic signal that plays a role in reproduction through the Hypothalamic-PituitaryOvarian axis. The aim of this study is to determine the effect of leptin on the levels of FSH and development of ovarian follicles of post-partum anestrus in Bali cattle. Method: Postpartum anestrus in Bali cattle were divided into three groups of nine; group 1 (control) was injected with physiological saline, group 2 (treatment I) and group 3 (treatment II) were injected with recombinant o-leptin 100 µg and 200 µg/head respectively. Injection was done twice with an interval of 12 hours. Blood sample was collected via the jugular vein at intervals of 12 hours before the start of treatment until signs of estrus had appeared. Follicle diameter was measured using ultrasonography before treatment and during estrus. Results: The average levels of FSH before treatment for group 1, group 2, and group 3 were 11.3 + 0.36 mIU/ml, 11.6 + 0.40 mIU/ml, and 11.4 + 0.28 mIU/ml respectively. While at the end of the research, the levels of FSH were 11:02 + 0.39 mIU/ml, 13.0 + 0.48 mIU/ml, and 13.47 + 1.05 mIU/ml respectively. Ovarian follicle diameter for group 1, group 2, and group 3 before treatment were 5.10 + 0.41 mm, 5.21 + 0.36 mm, and 5.00 + 0.37 mm respectively. Whereas at the end of the research, the ovarian follicle diameters were 4.92 + 0.40 mm, 8.37 + 0.43 mm, and 8.45 + 0.38 mm respectively. Conclusion: administration of o-leptin in postpartum anestrus of Bali cattle increases the level of FSH and ovarian follicle development.